2019
DOI: 10.1111/jcpt.13020
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled, open‐label early phase II trial comparing incidence of FOLFIRI.3‐induced diarrhoea between Hangeshashinto and oral alkalization in Japanese patients with colorectal cancer

Abstract: What is known and objective: We conducted a pilot clinical trial to investigate whether Hangeshashinto (TJ-14) could be substituted for oral alkalization in patients scheduled to undergo chemotherapy by FOLFIRI.3 regimen for colorectal cancer (CRC). Methods:Patients with CRC were randomized 1:1 to a TJ-14 (7.5 g/day) group or an oral alkalization (sodium bicarbonate, 1.8 g/day; ursodeoxycholic acid, 300 mg/day) group. The primary endpoint was incident of late-onset diarrhoea. A total of 30 patients were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The PRISMA flow diagram of the selected articles is presented in Figure 2 . After reconciliation, 40 articles were included in the analyses [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] ( File S1 Table S1 ). Of these 40 articles, 14 had a last-author affiliation from Asia (35%), 16 from Europe (40%), and 10 from North America (25%).…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow diagram of the selected articles is presented in Figure 2 . After reconciliation, 40 articles were included in the analyses [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] ( File S1 Table S1 ). Of these 40 articles, 14 had a last-author affiliation from Asia (35%), 16 from Europe (40%), and 10 from North America (25%).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 26 reports were screened by full-text review. Finally, three studies were selected for meta-analysis [ 16 , 17 , 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…In addition, Hangeshashinto is less expensive and could be a potential alternative to existing therapeutic agents for chemotherapy-induced diarrhea [ 14 - 16 ]. However, studies on the efficacy of Hangeshashinto in preventing chemotherapy-induced diarrhea have reported conflicting results [ 17 ]. Evaluating the effects of Hangeshashinto may reduce the use of and adverse events caused by drug therapy for chemotherapy-induced diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that intestinal alkalization by bicarbonate treatment showed a preventive effect for irinotecan-induced diarrhea in both in vivo and in vitro studies (57). In clinical studies investigating whether oral administration of bicarbonate (1.8-2.0 g/day) has preventive effects for irinotecan-induced diarrhea in patients with non-small cell lung cancer, small cell lung cancer, and colorectal cancer, no significant differences were observed in the effects of chemotherapy between the bicarbonate-treated and non-treated groups (58,59). However, the effects of bicarbonate administration as alkalization therapy requires further investigation, as the number of patients these previous were also small, the amount of bicarbonate consumption was low, and urine pH was not measured.…”
Section: Clinical Reports Of Alkalization Therapy For Cancermentioning
confidence: 99%